Chemical and structural stability of 2D layered materials - Wang, Xuewen; Sun, Yinghui; Liu, Kai (2d materials, 2019)
Two-dimensional (2D) layered materials have attracted intensive interests in the past decade. Their unique electronic, magnetic, optical, and mechanical properties render broad applications in various fields. Stability of these ultrathin materials has to be delicately considered because their structures and properties are subject to ambient conditions. In this work, we review the chemical and structural stabilities of versatile 2D layered materials, and summarize the ways to modify the materials for the enhancement of their stabilities. Our review not only provides deep understandings of the stability of 2D materials, but may inspire new ideas to improve the reliability and durability of related devices.